A decade of science for climate change adaptation and mitigation - Nowak, Andreea C.; Poulos, Allison; Chan, Yuling; Miller, Vail; Cramer, Laura K.; Schuetz, Tonya; Thornton, Philip K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This working paper synthesizes findings and reflections from an analysis of 300 CCAFS outcomes reported by project and program leaders between 2011 and 2020. The analysis, organized in the form of an outcome harvest, was aimed to distil typologies of outcomes achieved across geographies and groups of beneficiaries; the contributions of outcomes to program and institutional targets and sustainable development goals (SDGs) and targets; as well as key impact pathways derived from the activities, outputs and outcomes reported by CCAFS teams in relation to interventions targeting policy/investment and services/farm. The study also reveals examples of outcomes that progressed from one maturity level to the next, that expanded the scope of work, scaled to new geographies, or marked an increase in the number of innovations developed over the years, indicating a diversity of forms in which CCAFS outcome-oriented work has evolved towards increased impact.